Indonesia Systematic Country Diagnostic Update - World Bank (World Bank, Washington, DC, 2020)
Since Indonesia’s first Systematic Country Diagnostic (SCD) in 2015, the economy has grown steadily, poverty has declined to an all-time low and incomes of the bottom 40 percent have climbed. This SCD Update identifies four pathways leading to shared prosperity via higher productivity and better jobs, equal opportunities and greater resilience. Indonesia has made some progress in reforms along each of these pathways, but many challenges remain to be addressed. The four pathways not only remain highly relevant in the context of the COVID-19 pandemic but accelerating progress has become even more urgent.